STUDENTS’ ACCEPTANCE OF AI-BASED CHATGPT FOR EDUCATION: A COMPREHENSIVE ANALYSIS USING PLS-SEM - P. K. R., Goutham Krishna; Kuppuswamy, Sunitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial intelligence (AI) is transforming a number of aspects of human existence, including science, psychology, the arts, healthcare, education, and various other fields. The enormous influence of AI is seen in how it changes how we approach and engage with all of these sectors. One of the AI-based software programmes featuring a conversational AI interface is ChatGPT, an OpenAI chatbot. As one of the most groundbreaking applications, ChatGPT has attracted a lot of interest from the general public on a global scale. By using ChatGPT, the teaching and learning process in education could potentially be enhanced. Prior research mostly focused on academics’ and scientists’ opinions on ChatGPT and its future, while giving less importance to students’ perspectives on ChatGPT adoption. Therefore, the objective of this study is to understand the variables that influence students’ adoption of ChatGPT for their education. A "Students’ Adoption of AI" model, which helps in assessing behavioural intention and use behaviour, is proposed in this study and is based on the traditional Unified Theory of Acceptance and Use of Technology (UTAUT) model. The constructs of the proposed model are performance expectancy, effort expectancy, social influence, and facilitating conditions. The construct validity and reliability of the model are evaluated, and it is then further examined using PLS-SEM for hypothesis estimation and prediction.